Correlation between Family Support and Dietary Complience in Diabetes Mellitus Patience in Working Area of Community Center North Cimahi. - Argi, Argi Virgona Bangun; Galih, Galih Jatnika; Herlina, Herlina (JURNAL KESEHATAN KARTIKA, 2021)
Diabetes mellitus (DM) is a chronic disease where blood sugar levels (glucose) accumulate and exceed normal values. Diabetes mellitus divided into 2 type. Type 1 diabetes and type 2 diabetes, while the most common type of diabetes mellitus is diabetes type 2. About 90-95% of patients suffer from diabetes mellitus type 2. There are several management of diabetes mellitus one of them is diet management. Family support is one of the factors that support people with diabetes mellitus to obedient with their diet. The purpose of this research was to perceive the relationship between family support and dietary compliance in patients with type 2 diabetes melittus in working area of community center 15 North Cimahi. The method used is a correlation design using a cross sectional approach. The population in this research was 48 respondents of type 2 diabetes mellitus in working area of community center 15 North Cimahi. The sampling technique used in this study was total sampling with a sample of 48 patients. The instruments used in family support was the Hensarling Diabetes Family Support Scale (HDFSS) and dietary compliance instrument was Perceived Dietary Adherence questionnaire (PDAQ). Analysis of the data used in this research is univariat with normal distribution of familly support is 66 (Mean), compliance diet is 23 (Mean) and bivariat is chi square. Based on the results of this research, the results of good family support with adherence to a compliant diet (73.9%) and poor family support with non-adherent dietary compliance (60.0%). The results showed a significant relationship between family support and dietary compliance in type 2 diabetics in the working area of Community Center 15 North Cimahi with a p value of 0.038. Advice for people with diabetes mellitus to practice or apply the diabetes mellitus diet to control blood sugar levels and prevent complications.